Ecological inspirations of the TALC model of the tourism area life cycle - Szeligiewicz, Wojciech (Studia Ecologiae et Bioethicae, 2017)
Richard Butler’s model of the tourism area life cycle (TALC) proposes a defined image of qualitative changing of a number of tourists N over time within this area and of environmental, social, and economic processes simultaneously proceeding there. According to the model N increases up to the stagnation phase following an S-shaped curve. The curve is a solution to the logistic equation incorporated into the TALC model from ecology. The aim of this paper is to remind of the properties of the logistic model and underlying ecological assumptions, of some consequences that they may impose on the TALC model, and to tie some other aspects of the TALC model with ecology. In particular, a graph of the right-hand side of the logistic equation as a function of N is invoked labeled with the description of consecutive phases of the touristic area development reminding that the first “primary” stage of the area, i.e. when N is small, has the greatest tourist population growth per capita. Then, that there is a decline in the attractiveness of the area in spite of – according to the TALC scenario – provided facilities and investments. The same graph might be used to show some principal differences between eco-tourism and mass tourism. Moreover, the issues of population regulation, density-dependent self-regulation, Allee effect, carrying capacity, and r and K strategies were raised. It was also suggested that some experience from mathematical population modeling could be helpful in such considerations.